In-hospital mortality of acute coronary syndrome in elderly patients - Ahmed, Omima E. (Saudi Med J, 2019)
OBJECTIVES: To analyze predictors of death in elderly patients diagnosed with acute coronary syndrome (ACS). METHODS: A record-based study carried out between January 2016 and January 2018 at The central province in Saudi Arabia. All elderly patients (>75 years) with definite diagnosis of ACS were retrospectively included. Demographic data, echocardiographic, and angiographic parameters were reported. RESULTS: A total of 179 patients were enrolled, 129 (72%) were male. The mean age was 79±4.7 years. Approximately 102 (57%) patients were diagnosed with ST-segment elevation myocardial infarction (STEMI). Of all 125 (70%) underwent invasive coronary angiography, we found that 43 (24%) had significant single vessel disease (1VD), 29 (16.2%) had 2 vessel disease (2VD), and 41 (22.9%) had 3 vessel disease (3VD) or left main stenosis. During hospitalization 21 (11.7%) patients died, t-test analysis showed patients who died were significantly older (82±6.7 versus [vs.] 79±4.2 years, p=0.003). In addition we found that ejection fraction was lower in death group (30.2%±10.7) vs. (36.5%±1.1) in survivors, p=0.017); STEMI was more common in death group (90.5%) vs. (52.5%) in survivors, p=0.001); similarly, the prevalence of 3VD was higher in death group (38.1%) vs. (20.9%) in survivors, p=0.018). Importantly, PCI was not significantly different between death and survival groups (40% vs. 53.8%, p=0.177). A multivariate regression analysis demonstrated that predictors of death were: age (hazard ratio [HR], 1.214; 95% confidence interval [CI], 1.122-1.384; p<0.0001), intubation (HR, 10.106; 95% CI, 9.844-10.792; p<0.0001), and raised creatinine kinase-MB (CK-MB) (HR, 1.005; 95% CI, 1.002-1.013; p=0.04) predicted in hospital death. CONCLUSION: Older age, mechanical ventilation and raised CK-MB can significantly predict death in elderly patients (>75-year-old) diagnosed with ACS; nevertheless, PCI showed no survival benefits.